Factors Associated with Mental Health Risk among Final-Year University Students: A Cross-Sectional Study - Dilla Oktaviani; Sukendro Sukendro; Herwansyah Herwansyah; Asparian Asparian; Muldiasman Muldiasman; Willia Novita Eka Rini (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Mental health among final-year university students has become a significant concern due to increasing academic pressure during thesis completion. Objective: This study aimed to analyze factors associated with the risk of mental health disorders among final-year students of the Primary School Teacher Education Program (PGSD), Faculty of Teacher Training and Education, University of Jambi. Methods: A cross-sectional design was applied using total sampling of 203 students in semesters 7–14. The variables included academic stress, gender, organizational involvement, social media use, motivation, quality of supervisory relationship, and family economic status. Data were collected through self-administered questionnaires and analyzed using univariate analysis, chi-square tests for bivariate analysis, and logistic regression for multivariate analysis. Results and Discussion: The results showed that 51.7% of students were at risk of mental health disorders. Academic stress (POR=3.54; 95% CI=2.46–5.09), social media use (POR=1.74; 95% CI=1.30–2.34), motivation (POR=1.73; 95% CI=1.31–2.29), and quality of supervisory relationship (POR=1.57; 95% CI=1.20–2.07) were significantly associated with mental health risk. Gender, organizational involvement, and family economic status were not significantly associated. Academic stress was identified as the most dominant factor (aOR=13.75; 95% CI=6.46–29.27). Conclusion: Preventive efforts should prioritize academic stress management, responsible social media use, motivation enhancement, and improved supervision systems